Sustainable fabric printing by using pre-consumed cellulosic textile wastes: The effect of waste particle content - YILDIZ, ZEHRA; KARTAL, İLYAS; KOÇAK, EMİNE DİLARA; ERYILMAZ, OĞUZ (My University, 2024)
The textile industry generates significant amounts of waste, including yarn/fiber fluffs, fabric scraps, offcuts, etc. These wastes can be recycled and repurposed for usage in screen printing which is a versatile and cost-effective printing technique by producing high-quality prints. In this study, pre-consumed colored cotton wastes were milled into 30–70 μm particle size by using a miller. Then the colored waste particles were included in a commercial printing paste and applied on cotton fabrics via screen printing. Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) analysis, and energy dispersive spectrometer (EDS) were employed to observe the chemical changes in the printed textile fabrics. The printed fabrics were evaluated through color, wash/rub fastness, tensile strength, surface wettability, tactile, and air permeability properties. The dispersion quality of the waste particles on textile fabrics was observed by using light microscopy and scanning electron microscopy (SEM) images. The overall results demonstrate that a 10% amount of waste fibrous particle inclusion to the printing paste gave optimum results by means of dispersion quality of wastes, air permeability, and handle properties. Above 10% waste amounts, the waste particles cannot be dissipated well on the fabric surface, resulting in agglomerated and non-uniform printed areas. These findings hold substantial potential for promoting sustainable coloring applications by using colored pre-consumed textile wastes within the textile industry while maintaining high-quality fabric products.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Social Sciences and Humanities; Management; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Mühendislik; Ekonomi ve İş; ENERJİ VE YAKITLAR; İŞLETME; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); Social Sciences (SOC); ENGINEERING; ECONOMICS & BUSINESS; ENERGY & FUELS; BUSINESS; ENGINEERING, MANUFACTURING; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Genel Mühendislik; Strateji ve Yönetim; Sosyal Bilimler ve Beşeri Bilimler; Endüstri ve İmalat Mühendisliği; Renewable Energy, Sustainability and the Environment; Physical Sciences; General Engineering; Strategy and Management; Social Sciences & Humanities; Industrial and Manufacturing Engineering; Cotton fabric; Pre-consumed waste; Recycling; Screen printing; Sustainability; Waste cellulose